The anticoagulant rivaroxaban lowers portal hypertension in cirrhotic rats mainly by deactivating hepatic stellate cells. Issue 6 (2nd May 2017) - Vilaseca, Marina; García‐Calderó, Héctor; Lafoz, Erica; García‐Irigoyen, Oihane; Avila, Matías A.; Reverter, Joan Carles; Bosch, Jaume; Hernández‐Gea, Virginia; Gracia‐Sancho, Jordi; García‐Pagán, Joan Carles
Abstract : In cirrhosis, increased intrahepatic vascular resistance (IHVR) is the primary factor for portal hypertension (PH) development. Hepatic stellate cells (HSCs) play a major role increasing IHVR because, when activated, they are contractile and promote fibrogenesis. Protease‐activated receptors (PARs) can activate HSCs through thrombin and factor Xa, which are known PAR agonists, and cause microthrombosis in liver microcirculation. This study investigates the effects of the oral anticoagulant, rivaroxaban (RVXB), a direct antifactor Xa, on HSC phenotype, liver fibrosis (LF), liver microthrombosis, and PH in cirrhotic rats. Hepatic and systemic hemodynamic, nitric oxide (NO) bioavailability, LF, HSC activation, and microthrombosis were evaluated in CCl4 and thioacetamide‐cirrhotic rats treated with RVXB (20 mg/kg/day) or its vehicle for 2 weeks. RVXB significantly decreased portal pressure (PP) in both models of cirrhosis without changes in portal blood flow, suggesting a reduction in IHVR. RVXB reduced oxidative stress, improved NO bioavailability, and ameliorated endothelial dysfunction. Rivaroxaban deactivated HSC, with decreased alpha‐smooth muscle actin and mRNA expression of other HSC activation markers. Despite this marked improvement in HSC phenotype, no significant changes in LF were identified. RVXB markedly reduced fibrin deposition, suggesting reduced intrahepatic microthrombosis. Conclusion : RVXB decreases PP in two rat models of cirrhosis. This effect is mostly associated with decreased IHVR, enhanced NO bioavailability, HSC deactivation, and reduced intrahepatic microthrombosis. Our findings suggest that RVXB deserves further evaluation as a potential treatment for cirrhotic PH. (Hepatology 2017;65:2031‐2044).